PM.97 Neural Tube Defects (NTDs) in 21St Century Ireland: A Tertiary Referral Centre's Experience. (26th April 2013) - Monteith, C; Cooley, S; Smith, S Coulter-
Abstract : The incidence of NTDs in Ireland has declined over the past two decades from 4.8/1000 births in 1980 to 0.8–1.5/1000 births in 2001 1 Preconceptual folic acid is accepted to reduce the incidence of NTDs however, 50% of pregnancies are unplanned. 2 We reviewed the cases over the past three years, their gestation at diagnosis and outcome in conjunction with EUROCAT reporting. All cases of NTDS were identified from the Fetal Assessment Unit records between 2009 –2011. Maternal notes were reviewed to assess demographics and pregnancy outcome. In total 45 cases of NTD were detected. The overall incidence in our population 1.44/1000 births. Table 1 illustrates the subcategories of NTD diagnosed with the continuation rates. 53.3% (n = 24) delivered in the Rotunda, a further 42.2% (n = 19) didn't re attend for antenatal care and 4.4% (n = 2) returned to other units. Those women who didn't attend for subsequent care were statistically more likely to have diagnosis earlier in the second trimester (16 +3) than those who delivered in the Rotunda (23 +1) p value <0.0001. There was a significant difference in the average gestation of diagnosis between the group of women who chose to not continue their pregnancies compared to those who do continue. This suggests that early diagnosis affords more options to women of infants with NTD and suggests that second trimester scanning may be warranted, particularly in high-risk groups. 3 The high incidence of NTD and the poor obstetric outcome again raises the argument for food fortification in Ireland. References: Ward M et al . Folic acid supplements to prevent neural tube defects: trends in East of Ireland 1996–2002. Ir Med J 2004:274–6. Report of the Implementation group on folic acid food fortification to the Department of Health and Children 2008. McAuliffe et al . Ultrasound detection of fetal anomalies in conjunction with first-trimester nuchal translucency screening: A feasibility study. Am J Obstet Gynecol 2005;193:1260–5.